Stressful incidents, stress and coping strategies in the pre-registration house officer year - Paice, Elisabeth; Rutter, Harry; Wetherell, Mike; Winder, Belinda; McManus, I C (Medical education, 2002)
Context Previous studies have drawn attention to the stresses experienced by doctors in their first year. Objectives To gain a deeper understanding of the causes of stress in newly qualified doctors, how they cope, and what interventions might make the year less traumatic. Design Postal questionnaire. This study focused on an open question asking about a stressful incident, the coping strategy used to deal with it, stressors in general and current levels of stress using the General Health Questionnaire. Setting 336 hospitals throughout the United Kingdom. Subjects A cohort of doctors followed from the time of their application to medical school, studied towards the end of their pre‐registration year (n=2456). Results The response rate to the questionnaire was 58·4%. The incidents were categorised into the major groups Responsibility (33·6%), Interpersonal (29·7%), Overwork (17·0%), Death and disease (13·0%), and Self (6·7%). GHQ revealed psychological morbidity in 31% of respondents. Stress levels were highest in those reporting an incident about Responsibility or Self, lowest in those describing Death or disease. Stressors in general and preferred coping strategies differed between the groups. Conclusion The incidents suggested the following interventions to reduce stress: better supervision in the first few weeks in post, at night, and for medical problems on surgical wards; more attention to avoiding sleep deprivation; more time for discussion with colleagues at work; more personal time with friends and family. The choice of incident described was influenced by the personal characteristics of the respondent.